A case of intradiaphragmatic bronchogenic cyst with an abnormally high serum level of CA19‐9. Issue 10 (23rd September 2021) - Kamimura, Go; Ueda, Kazuhiro; Suzuki, Soichi; Aoki, Masaya; Nagata, Toshiyuki; Sato, Masami
Abstract: Bronchogenic cysts that occur within the diaphragm are rare and difficult to diagnose preoperatively. We experienced the case of a patient with an abnormally high serum carbohydrate antigen 19‐9 (CA19‐9) level before surgery. The diagnosis of intradiaphragmatic bronchogenic cyst was made at the time of surgery. The patient was a 50‐year‐old woman with upper abdominal pain with an incidentally elevated serum CA19‐9. Although the tumour location could not be established on images, a tumour within the diaphragm was confirmed during the operation. The diaphragm was incised and the tumour was removed together with the capsule. Bronchial cysts were diagnosed histopathologically, and immunohistochemical examination revealed that the bronchial epithelial cells were positive for CA19‐9. When managing patients with bronchogenic cysts in the diaphragm, it is difficult to make a preoperative diagnosis or determine the location of the tumour; thus, careful planning is required before surgery. Abstract : Bronchogenic cysts that occur within the diaphragm are rare and difficult to diagnose preoperatively. Here, we report the case of a patient with an abnormally high serum carbohydrate antigen 19‐9 (CA19‐9) level before surgery. The diagnosis of intradiaphragmatic bronchogenic cyst was made during surgery. When managing patients with bronchogenic cysts in the diaphragm, a preoperative diagnosis or location of the tumour can be difficult; thus, careful planning is required before surgery.